The Influence of Financial Literacy and Behavior In Using Fintech Payments on The Financial Management of Jabodetabek Students - Nuriza Nenden Irawan; Rindang Matoati (The Management Journal of Binaniaga, 2021)
The low financial literacy of Indonesian students at 23.20% and the emergence of a technology called fintech payment which tends to change individuals encourages the creation of a cashless society. The younger generation has great potential in increasing the level of financial literacy and the ability to use financial services optimally which will have an impact on financial management. This research aims to 1) analyze the level of financial literacy, the level of behavior in using fintech payments, and the level of financial management in students in Jabodetabek, 2) analyze the effect of financial literacy on the financial management of students in Jabodetabek, and 3) analyze the effect of using fintech payments on financial management. students in Jabodetabek. The population of this research is Jabodetabek bachelor degree students. The sampling technique used is non-probability sampling with purposive sampling technique with 200 respondents. The method of analysis used descriptive analysis and PLS Structural Equation Modeling (SEM). The results showed that the average level of financial literacy for Jabodetabek students was 81.09% and classified as well literate, the behavioral level of using fintech payments was 84.43% and classified as very high, and the level of financial management for Jabodetabek students was 80.93% and classified as very good. Financial literacy and the behavior of using fintech payments partially have a positive and significant influence on financial management.